The Power of Connections : How a Novel Canadian Men’s Wellness Program is Improving the Health and Well-Being of Indigenous and Non-Indigenous Men ... - Efimoff, Iloradanon; Patrick, Lyana; Josewski, Viviane; Gross, Paul; Lambert, Sandy; Smye, Victoria (Western University, 2022)
The DUDES Club is a novel men’s health and wellness organization founded in 2010 in Vancouver, BC. Since 2017, the DUDES Club has rapidly expanded in Northern BC and, with the help of a partnership with the First Nations Health Authority, has grown to include 40 sites in British Columbia and 2 sites nationally. In this study, we analyze data from interviews (n = 5) and 15 focus groups (n = 101) conducted as part of a program evaluation with DUDES Club members, Elders, providers, and health care professionals. We focus on men’s experiences with the DUDES Club to identify four main themes in the data: brotherhood and community, accessible health care information, disrupting colonial constructions of masculinity, and systemic and structural challenges. We conclude with policy recommendations. ...